“Have You Volunteered?”: Or Why Students Become Volunteers - T. A. Shulgina; N. A. Ketova (Высшее образование в России)
The study highlights the importance of motivating students to participate in volunteering as it is viewed as an effective tool of modern management at the University. On the example of volunteers of Kursk State Medical University, the article reveals common motives for their participation in volunteer activity and the potential of volunteering to develop general cultural (universal) competencies. So, the researchers identify among the leading motives the following: altruistic motives, motives of personal development, involvement, self-realization, communication. The questionnaire of volunteers made it possible to confirm the theoretical conclusions obtained from the literature review, and enhances the authors’ conclusions on the need for constructing the sociocultural environment at the University. The authors believe that the participation in the University’s volunteer projects creates conditions for students’ self-realization and self-development, which ultimately contributes to the development of their general cultural (universal) competencies as well as to the realization of the objectives of the state youth policy by the University. Considering volunteering as an innovative form of educational work, the researchers focus on the fact that the study of the motives of active volunteers allows modern leaders of higher education to more clearly create conditions for meeting the needs of volunteers, combining the interests ofan individual with public goals.